If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 + q = 43 Solving 30 + q = 43 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + q = 43 + -30 Combine like terms: 30 + -30 = 0 0 + q = 43 + -30 q = 43 + -30 Combine like terms: 43 + -30 = 13 q = 13 Simplifying q = 13
| z-122=8 | | 6x^2=13m+28 | | 2^1-×^2=1/8 | | 9=2/3x-1 | | 3/4x=0/1 | | 2=0.021lt | | -2x-6=2-4x-(1-x) | | 13x-12=-6y | | 2-2x/4=6x/6 | | x^3-4x^2-64x+256=0 | | 7(x+7)=7(x-3) | | 150=(2x+15)(2x+10) | | 1/2x+1/3=2/3 | | 0.4(x-4)=3.6 | | 5y-1-3y=5/1/5 | | N^2+4n=13 | | 6h+3.7=52.7 | | 4n-12=48+2n | | 5y-20x=10 | | 0=3sinx-1 | | 4=.25(2-4.3) | | 208=(10+2x)(8+2x) | | 10x+20=70 | | 8x-18=6y+3 | | 10+-5+w=30 | | x^4-5=4x^2 | | 0.5x+1.3=3.1 | | 2+4(n+2)-2n=0 | | (-6p+7)-4=76 | | n^2+4=13 | | x/4-6=12 | | m+100/12=15 |